Pengaruh Store Atmosphere dan Hedonic Shopping terhadap Impulse Buying - Andi Anggi Monica; Niar Astaginy; Hendrik Hendrik (Politeknik Baubau, 2023)
This study aims to determine the effect of store atmosphere and hedonic shopping on impulse buying in consumers of MR DIY Kolaka stores. This research is a quantitative study with an eksolanatory research approach using a questionnaire as an instrument. The population in this study were all consumers of MR DIY Kolaka stores with 120 respondents using purposive sampling technique, namely the technique of determining certain criteria. Testing research instruments using validity tests and reliability tests with SPSS 25.0. The data analysis technique used in this study is the measurement model test (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the results of the study, it is known that there is a positive and significant influence between the Store Atmosphere variable on Impulse Buying at MR.DIY Kolaka Store Consumers, which is indicated by the t-statistic value of 4.293 with a P-Value of 0.000. While the Hedonic Shopping variable on Impulse Buying in MR.DIY Store consumers has a positive and significant effect, which is indicated by the t-statistic value of 5.792 with a P-Value of 0.000.